METAMORPHIC-HOSTED PYROPHYLLITE AND DICKITE OCCURRENCES FROM THE HYDROUS AL-SILICATE DEPOSITS OF THE MALATYA-PÜTÜRGE REGION, CENTRAL EASTERN ANATOLIA, TURKEY - Bozkaya Ö.; Yalçin H.; Başibüyük Z.; Bozkaya G. (My University, 2007)
Hydrous Al-silicate deposits are found to the south of Pütürge in Malatya city, Turkey. The surrounding rocks consist of mylonitic granitic gneiss overlain by muscovite gneiss with kyanite-bearing metabasic schist lenses on top which are cut by silica veins containing prismatic tourmaline and speculante. Pyrophyllite is found within kyanite gneisses overlying the granitic gneisses. Fibrous, platy pyrophyllite is developed along the edges and cleavage planes of kyanite, whereas platy bunches of dickite occur as replacements of the relict kyanites as well as crack- and pore-fillings. Rocks forming the hydrous Al-silicate deposit contain 2M1 pyrophyllite, alunite, topaz, paragonite, dravite, dumortierite, chlorite and epidote as early hypogene minerals, and 2M1 dickite, diaspore, gibbsite, speculante, goethite and crandallite/goyazite as late hypogene minerals. On the basis of fluid inclusion and stable isotope data, it is estimated alterations to pyrophyllite and kaolinite occurred at temperatures are of 150 and 100°C, respectively, the minerals being formed by meteoric waters interacting with metamorphic rocks. Trace and REE variations are highly distinctive in terms of enrichment of most trace elements in pyrophyllite, whereas REEs are clearly abundant in dickite, indicating different conditions during formation such as early and late hypogene processes. The pyrophyllitic alteration took place in the late Cretaceous (69–71 Ma), whereas kaolinization occurred later.
Keywords: DICKITE; GEOCHEMISTRY; HYDROTHERMAL ALTERATION; MINERALOGY; PYROPHYLLITE; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая